Osteoporosis due to the treatment of some neoplasms - Nowak-Markwitz, Ewa; Kaplenko, Irina; Przybylski, Marcin; Spaczyński, Marek (Menopause Review/Przegląd Menopauzalny, 2003)
This article describes the most important issues related to osteoporosis secondary to neoplastic diseases or their treatment with special focus on their pathogenesis and clinical consequences and influence on quality of the patient’s life. But the most important aim of this article is to identify the higher risk groups and to remind of this problem to a clinician, who is in has permanent contact with neoplastic disease’s problem.